KOMUNIKASI INTERPERSONAL PENGACARA DENGAN KLIENNYA DALAM PERKARA TINDAK PIDANA KORUPSI DI RAMADHAN DAN RAJUL LAW FIRM PEKANBARU - Putra, Yogo Pratama; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
When someone was involved in corruption cases, then that person need a lawyer who can help to solve the problem. To resolve the case is necessary for good interpersonal communication that is conducted by lawyers to their clients. This study was conducted to determine how the openness, emphaty, possitiveness, supportiveness, and equality of the lawyers to their clients in resolving cases of corruption.This study used qualitative research methods and conducted with social penetration theory. A total of informants in this research are 4 people, 2 of them are lawyers and the 2 are clients. are a lawyers and they clients. Data collection is done by interview, observation, and documentation.The resuts of this study indicate that the attitude of openness is lawyers want to listen to their clients, emphaty that lawyers understand the state of their clients, possitiveness that lawyers spoke with a smile and friendly, supportiveness that lawyers help clients make a defense attorney, and equality that lawyers makes a family atmospher conducted a lawyers to their clients in the corruption case.Keyword : Lawyer,interpersonal communication, Client, corruption